Третий в пятом ряду: повести и рассказы : [для старшего школьного возраста] / Анатолий Алексин - Алексин Анатолий Георгиевич (Молодая гвардия, 1977)
Экземпляры: КХ (20120328) / Инвентарный номер: 656640 / Сис.шифр: Р2 / Авт.знак: А 48 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4